A környezeti piac néhány munkaerőpiaci és logisztikai összefüggése az elmúlt évtizedben - Gál, József (Jelenkori Társadalmi és Gazdasági Folyamatok, 2007)
Environmental market is much more than environmental protection. We must survey it in its economical, sociological etc. aspects. In my paper I try to find some interesting connecting points how to meet labour market, logistics of material, people and knowledge. Number of employees in this sector is increasing fluently, but you can see big gap among different parts of Europe. We know pollution and environmental protection do not stop at frontiers of countries, therefore must understand flows and find common solutions.